Reassessing the nuremberg military tribunals: transitional justice, trial narratives, and historiography - Priemel, Kim C; Stiller, Alexa (Studies on war and genocide, 2012)
For decades the history of the US Military Tribunals at Nuremberg (NMT) has been eclipsed by the first Nuremberg trial-the International Military Tribunal or IMT. The dominant interpretation-neatly summarized in the ubiquitous formula of "Subsequent Trials"-ignores the unique historical and legal character of the NMT trials, which differed significantly from that of their predecessor. The NMT trials marked a decisive shift both in terms of analysis of the Third Reich and conceptualization of international criminal law. This volume is the first comprehensive examination of the NMT and brings together diverse perspectives from the fields of law, history, and political science, exploring the genesis, impact, and legacy of the twelve Military Tribunals held at Nuremberg between 1946 and 1949.